TUMORS OF THE NONPIGMENTED EPITHELIUM OF THE CILIARY BODY: The Lorenz E. Zimmerman Tribute Lecture. Issue 5 (May 2015) - Shields, Jerry A.; Eagle, Ralph C.; Ferguson, Kyle; Shields, Carol L.
Abstract : Background: In 1970, Dr. Lorenz Zimmerman delivered the Norman McAlister Gregg Lecture entitled "The remarkable polymorphism of tumors of the ciliary epithelium." Therein, he proposed a classification of these tumors that included congenital lesions (mainly medulloepithelioma) and acquired lesions (mainly adenoma and adenocarcinoma). The classification was based on histopathologic observations without detailed clinical information. Methods: Review of the published literature and personal experience with tumors of the nonpigmented ciliary body epithelium. Results: Since 1970, further observations through clinical examination and advanced testing with ultrasound biomicroscopy, anterior segment optical coherence tomography, and magnetic resonance imaging have expanded our knowledge regarding tumors of the nonpigmented ciliary body epithelium. Regarding medulloepithelioma, we have learned of the common associated features of neovascular glaucoma, retrolenticular neoplastic or vascular cyclitic membrane, intralesional cysts, response to radiotherapy, and association with Dicer-1 mutation. Regarding adenoma/adenocarcinoma, improved management with surgical resection (sparing globe) can be achieved. Fuchs adenoma, also termed coronal adenoma, is commonly found histopathologically, despite its rare clinical visualization, and should be added to the Zimmerman classification. Conclusion: Since Zimmerman's report on histopathologic features of tumors of the nonpigmented ciliary body epithelium, there have been numerous publications and further observations on the clinical features and management of these intriguing neoplasms. Abstract : Since Zimmerman's report on histopathologic features of tumors of the nonpigmented epithelium of the ciliary body, there have been further observations regarding clinical and histopathologic features of these tumors and relationship to systemic cancer predisposition syndrome.